FERRIC-FERROUS EQUILIBRIA IN K2O-FEO-FE2O3-SIO2 MELTS - Tangeman J.A.; Lange R.; Forman L. (My University, 2001)
Seventy-five K2O-FeO-Fe2O3-SiO2 liquids were equilibrated in air between 1123°C and 1596°C. The bulk compositions of the quenched glasses range from 35 to 85 wt.% SiO2, 3 to 41 wt.% Fe2O3, 0 to 5 wt.% FeO, and 11 to 34 wt.% K2O. Despite the volatilization of significant amounts of potassium in many of the high-temperature runs, no gradients in K2O, SiO2, or total iron were observed from electron microprobe transects of the 75 quenched glass beads. This result strongly suggests that the rate of K diffusion in the melt is faster than the rate of K volatilization at the gas/melt interface. The individual quenched glass beads were homogenous in their ferric-ferrous ratios as well, which further suggests that iron-redox equilibrium was achieved in these experiments. The ferric-ferrous data were used to derive a symmetric, regular solution model, with a standard error of 0.18 wt.% in the prediction of FeO in peralkaline K2O-FeO-Fe2O3-SiO2 liquids. Compositional trends for redox equilibrium in the potassic silicate liquids contrast with those found in sodic and calcic silicate liquids, as well as magmatic liquids. The effect of increasing K2O is to decrease the ferric-ferrous ratio in peralkaline, iron-rich (>3 wt.%), K2O-FeO-Fe2O3-SiO2 liquids. These results are discussed in terms of three compositional effects that influence iron-redox equilibria in silicate melts: 1) charge-balancing of Fe3+; 2) coordination change of Fe3+; and 3) the activity of O2- in the melt.